Reflections on bridging the academic/practitioner divide: "Drugs and Thugs" as a case study. Issue 2 (July 2019) - Straussman, Jeffrey D
The academic/practitioner divide is real. Having observed and participated in this divide over four decades it seems as if the same issues get repeated over and over. This paper offers one approach that was used several years ago. The "case" is a collaboration between a recently hired Professor of Practice and the author, a full professor with only limited government experience. There were two main challenges in the relationship. The diplomatic had to adjust to a different organizational culture and the academic had to adjust to contact he wasn't familiar with. A new elective course was developed called, Drugs, Crime, and Terrorism. I describe this process and draw lessons about the value of this type of experience for faculty, practitioners, and professional education.